Shared decision making: what do clinicians need to know and why should they bother?. Issue 1 (7th July 2014) - Hoffmann, Tammy C; Légaré, France; Simmons, Magenta B; McNamara, Kevin; McCaffery, Kirsten; Trevena, Lyndal J; Hudson, Ben; Glasziou, Paul P; Del Mar, Christopher B
Summary: Shared decision making enables a clinician and patient to participate jointly in making a health decision, having discussed the options and their benefits and harms, and having considered the patient's values, preferences and circumstances. It is not a single step to be added into a consultation, but a process that can be used to guide decisions about screening, investigations and treatments. The benefits of shared decision making include enabling evidence and patients' preferences to be incorporated into a consultation; improving patient knowledge, risk perception accuracy and patient–clinician communication; and reducing decisional conflict, feeling uninformed and inappropriate use of tests and treatments. Various approaches can be used to guide clinicians through the process. We elaborate on five simple questions that can be used: What will happen if the patient waits and watches? What are the test or treatment options? What are the benefits and harms of each option? How do the benefits and harms weigh up for the patient? Does the patient have enough information to make a choice? Although shared decision making can occur without tools, various types of decision support tools now exist to facilitate it. Misconceptions about shared decision making are hampering its implementation. We address the barriers, as perceived by clinicians. Despite numerous international initiatives to advance shared decision making, very little has occurred in Australia. Consequently, we are lagging behind many other countries and should act urgently.